Carbon footprint analysis in the aquaculture industry: Assessment of an ecological shrimp farm. (1st December 2017) - Chang, Ching-Chih; Chang, Kuei-Chao; Lin, Wen-Chun; Wu, Ming-Hsi
Abstract: The study uses life cycle assessment to analyze the carbon footprint of an ecological shrimp farm located at Yijhu, Taiwan. The procedural study contains primary and secondary data. The quantization procedure follows the ISO/TS 14067. This study aims to estimate the white shrimp full life cycle carbon footprint using a function unit per kilogram. SimoPro 8.0 is used to calculate the carbon footprint in this study. The results show that the life cycle total carbon footprint of white shrimp is 6.9389 kgCO2 e/kg. The top five factors in terms of carbon emissions were as follows: electricity (2.0093 kgCO2 e/kg, 29.39%), feed (1.6395 kgCO2 e/kg, 23.98%), indirect raw materials (1.4782 kgCO2 e/kg, 21.62%), waste treatment (0.7783 kgCO2 e/kg, 11.40%) and transport and refrigerant (0.7524 kgCO2 e/kg, 11.01%). The results showed that wastewater treatment is one of the emission hotspots over the whole life cycle. To conclude, the carbon footprint of the shrimp supply chain can be reduced by employing energy-conserving technology, by utilizing simple wastewater treatment procedures, and by using territorial plants as feed, and such moves could help this industry achieve its goals with regard to a sustainable environment. Highlights: The carbon footprint of an ecological shrimp farm is studied. The lifecycle total carbon footprint of white shrimp is 6.9389 kgCO2 e/kg. The greatest emissions come from the electricity (2.0093 kgCO2 e/kg). Alternative energy solutions should be encouraged in the aquaculture industry.